FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN OPERATOR PENGOPERASIAN HEAT RECOVERY STEAM GENERATOR (HRSG) TERHADAP INSTRUKSI KERJA DI PT X SEMARANG - Kholid Saifulloh; Bina Kurniawan; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2019)
Companies engaged in electricity include the risk of high risk of fire and explosion. Compliance with work instructions has an important role in preventing work accidents. PT X Semarang is a power plant company and in the production process uses a Heat Recovery Steam Generator (HRSG) engine which has the potential for fire and explosion hazards. The purpose of this study is to describe the factors that influence the compliance of the Heat Recovery Steam Generator (HRSG) operating operator against work instructions at PT X Semarang. This research is a descriptive study with a qualitative approach. The main informants were four HRSG operators and triangulation informants consisting of two senior supervisors and one K3 executive. The instrument of this study uses the in-depth interview guidelines. The results of the study show that the operator's knowledge of work instructions is good about the notion of work instructions, benefits, objectives, flow of operations of the HRSG, and the impact it has on. The availability of work instructions at PT X Semarang is good based on work instructions that are already available in document form and reviewed regularly. The socialization of work instructions has been good by carrying out every night shift review activity, morning briefings, and knowledge sharing by explaining the changes in work processes before and after in accordance with the conditions in the field. Companies regarding HRSG operating instructions should be reviewed if there are changes in tools or processes in the work.